A novel fuzzy MCDM model for inventory management in order to increase business efficiency - Vukasović, Dragan; Gligović, Dejan; Terzić, Svetlana; Stević, Željko; Macura, Perica (Technological and Economic Development of Economy, 2021)
Appropriate implementation and organization of logistics activities greatly contributes to the creation of a better business environment in companies. This is reflected in increased business efficiency, cost rationalization, increased productivity and better overall quality. In order for a company to achieve sustainability of its business and its competitiveness, the link between the marketing logistics system and other logistics subsystems is particularly evident. Thereby, it is necessary to lead proactive management with a focus on key resources. In this paper, two novel integrated models in fuzzy form have been created. The first model includes the integration of the fuzzy Full Consistency Method (fuzzy FUCOM) and the fuzzy Evaluation based on Distance from Average Solution (EDAS) method for sorting 78 products regarding the following four criteria: quantity, unit price, annual procurement costs and demand. The second model involves the integration of the fuzzy FUCOM method and ABC analysis for the purpose of inventory sorting considering different significance of criteria. A range of values has been formed for each product category within the fuzzy FUCOM and fuzzy EDAS models, on the basis of which their sorting has been performed. The advantages and verification of the developed integrated fuzzy models have been performed through comparison with former traditional approaches. It has been determined based on an extensive sensitivity analysis that the developed models have better performance compared to the existing ones. First published online 09 March 2021